Evaluasi Ketercapaian Standar Penjaminan Mutu Kinerja Penelitian, Pengabdian Dan Hak Paten Program Studi PGMI UMmagelang - Oktradiksa, Ahwy; Shalikah, Norma Dewi; Nugroho, Irham; Sari, Kanthi Pamungkas; Aufa, Minzani; Iman, Muis Sad (Jurnal Penjaminan Mutu, 2019)
Muhammadiyah University of Magelang (UMMagelang) with Study Program Madrasah Ibtidaiyah Teacher Education (PGMI) has a vision "To become a superior and nationally Islamic study program in 2024 the development of Islamic science in the field of teacher professional education (MI/SD)". In order to realize the performance and improvement of PGMI Study Program lecturers based on 17 quality objectives set out in the appendix of the study program vision, in this article only the criteria for research and service are delivered, the PGMI UMMagelang study program refers to the UMMagelang research roadmap. In the last 3 years, lecturers of PGMI were involved in 28 Research and Service Titles. LP3M UMMagelang Internal Funding: 8 Title University Vision Revitalization Program (PRVI) and 9 University Partnership Program (PKU) titles. External Funding for DRPM Kemenristekdikti: 2 titles of Higher Education Leading Basic Research (PDUPT), 1 title of Grant DIPA Kopertais Wilayah X Central Java, 1 title Grant of Magelang regency, 1 title Community Partnership Program (PKM), 1 title Village Partner Development Program (PPDM)